Diatom Biodiversity and Speciation Revealed by Comparative Analysis of Mitochondrial Genomes - Wang, Yichao; Liu, Shuya; Wang, Jing; Yao, Yanxin; Chen, Yang; Xu, Qing; Zhao, Zengxia; Chen, Nansheng (Frontiers in Plant Science, 2022)
Diatoms (Bacillariophyta) constitute one of the most diverse and ecologically significant groups of phytoplankton, comprising at least 100,000 species in three classes Bacillariophyceae, Mediophyceae, and Coscinodiscophyceae. Common molecular markers including 18S rDNA, 28S rDNA, ITS, rbcL, and cox1 are usually inadequate for distinguishing diatom species. Organelle genomes including mitochondrial genomes (mtDNAs) have been proposed to be “super barcodes” for distinguishing diatom species. However, the number of reported diatom mtDNAs is currently limited. Here, we constructed complete mtDNAs of 15 diatom species including five Coscinodiscophyceae species (Guinardia delicatula, Guinardia striata, Stephanopyxis turris, Paralia sulcata, and Actinocyclus curvatulus), four Mediophyceae species (Hemiaulus sinensis, Odontella aurita var. minima, Lithodesmioides polymorpha, and Helicotheca tamesis), and six Bacillariophyceae species (Nitzschia ovalis, Nitzschia sp., Nitzschia traheaformis, Cylindrotheca closterium, Haslea tsukamotoi, and Pleurosigma intermedium). In addition to their value as super barcodes, mtDNAs are also valuable in evolutionary studies. Comparative analysis of mtDNAs revealed extensive genome rearrangement events, gene duplications, gene losses, and gains and losses of introns. Duplication of cox1 was discovered for the first time in diatoms in Nitzschia traheaformis and Haslea tsukamotoi. Synteny analysis of mtDNAs uncovered extensive genome rearrangement events including translocations and/or inversion at the class level, while high conservation at the order level. Molecular dating analysis revealed that three diatom classes split 100 Mya and many diatom species appeared since 50 Mya. More diatom mtDNAs representing different orders will play great dividends to explore biodiversity and speciation of diatoms in different ecological regions.